Coevolution of Giant Molecular Clouds, Filaments, and Clumps as a Function of the Dense Gas Mass Fraction - Wenjun Zhang; Jianjun Zhou; Jarken Esimbek; Willem Baan; Xindi Tang; Dalei Li; Yuxin He; Gang Wu; Dongdong Zhou; Yingxiu Ma; Kadirya Tursun; Weiguang Ji; et al. (The Astrophysical Journal Supplement Series, 2024)
We investigate the evolutionary dynamics with archival continuum and line data of 27 giant molecular clouds (GMCs) in the Milky Way, focusing on their influence on star formation. Examining the dense gas mass fraction (DGMF) among the GMCs, we categorize them into low-DGMF (DGMF < 20%), medium-DGMF (20% < DGMF < 60%), and high-DGMF (60% < DGMF) groups. The analysis uncovers systematic trends in the free-fall time, virial parameter, surface density, star formation rate (SFR), SFR per unit area (Σ _SFR ), and star formation efficiency for dense gas as the DGMF increases within GMCs. We identified 362 filaments and 3623 clumps within the GMCs. Increasing DGMF correlates with higher proportions of star-forming clumps and clumps capable of forming massive stars. Clump properties such as hydrogen number density and surface density increase with DGMF, while the mass and radius decrease. The dust temperature and virial parameters show no significant variation with DGMF. We also observe convergence in the hydrogen number density and dust temperature between star-forming and starless clumps with rising DGMF. Filaments are found to be spatially associated with clumps capable of forming high-mass stars, with those on filaments exhibiting greater mass, radius, hydrogen number density, surface density, and velocity dispersion. Moreover, filaments hosting clumps capable of forming high-mass stars demonstrate larger mass, length, and line mass. In summary, this comprehensive analysis of GMCs, filaments, and clumps supports the notion of a multiscale coevolution process. From GMCs to filaments and subsequently to clumps, the DGMF emerges as a valuable tracer for understanding the evolutionary trajectory of GMCs and the processes governing their development.